Post Chickenpox Sequel in Children: Three Distinct Presentation (Anwer Khan Modern Medical College Journal, 2017)
Varicella (Chicken pox) is a common paediatric disease which usually self-limiting and resolves without sequelae. Complications are not common in immune-competent children. We present a series of three cases with rare complications following chicken pox, presented with distinct diagnoses,the etiology for which was established on the basis of history, examination and serological tests . The first two cases had neurological complications and the third case was a diagnosed case of hemophilia and presented with osteomylitis. All these complications developed following chicken pox. The cases responded differently to treatment and the patients were left with minimum disability.Anwer Khan Modern Medical College Journal Vol. 7, No. 2: Jul 2016, P 45-52